PENGARUH HARGA POKOK PRODUKSI TERHADAP LABA PADA PT. SEMPURNAINDAH MULTI NUSANTARA - KARYADI; ENTANG SETIAWAN, SILVIA DEWI ENTANG SETIAWAN, SILVIA DEWI (EKBIS (Ekonomi & Bisnis), 2018)
This study aimed to know how much the influence cost of production to profit at PT. Sempurnaindah Multinusantara period of 2011-2015. The research method used descriptive method with quantitative approach. Data was collected through observation, interview, and library research. Analysis technique used pearson product moment correlation analysis, simple linear regression analysis, coefficient of determination and hypothesis testing (T test). The result of showed that pearson product moment correlation analysis 0.968, the result of simple linear regression analysis Y = 148.448,336 + 0,21X, the result of determination coefficient 93,7% and result of T test ???????????????????????? > ???????????????????????? (6,700 > 3,182) and sig 0,007 < 0,05 concluded that the cost of production affect the Profit. Suggestions for PT. Sempurnaindah Multinusantara should be able to suppress and minimize the price of raw materials which each year has an increase that affects the determination of the cost of production but must be adjusted with quality on the raw material, and increase sales, So the profit earned more increases.